Comparison of the Impacts of Auriculotherapy with Electrical Stimulation and Vaccaria Seeds on Colposcopy Pain: A Randomized Clinical Trial - Samaneh Jouya; Nahid Golmakani; Seyed Reza Mazloum; Hamid Abdi; Zohreh Yosefi (Mashhad University of Medical Sciences, 2018)
Background: Colposcopy is an invasive medical procedure, which involves pain and discomfort. Auriculotherapy is a medical technique that can facilitate the reduction of pain. Aim: The aim of this study was to compare the impacts of auriculotherapy with electrical stimulation and Vaccaria seeds on colposcopy pain. Method: This controlled randomized, clinical trial was conducted on 93 females undergoing colposcopy in Ghaem Hospital, Mashhad, Iran, in 2017. The study population was selected through convenience sampling technique, and then randomly assigned into three groups, namely transcutaneous auricular stimulation (TAS), Vaccaria seeds, and placebo. The TAS group was subjected to electrical stimulation at four auricular acupuncture points 40 min before colposcopy, using a Pointer Excel stimulator (2 Hz). In the Vaccaria seed group, the seeds were fixed on the same acupoints three days prior to colposcopy. The participants were asked to press each point for 1 min, three times a day. The placebo group were provided with three adhesive patches without any seeds. After colposcopy, pain intensity was monitored using the visual analog scale. Data analysis was performed using Kruskal-Wallis and exact Chi-square tests in SPSS software, version 22. Results: The three groups were comparable in terms of the demographic data (P>0.05). The mean pain intensities in theTAS, seed, and placebo groups were 49.0±24.2, 49.5±26.0, and 65.1±26.6, respectively. A significant difference was observed among the three groups regarding the pain intensity (P=0.02). There were also significant differences between the TAS and placebo groups (P=0.01) and between seed and placebo groups in this respect (P=0.02). However, the TAS and seed groups showed no significant difference in this regard (P=0.94). Implications for Practice: The use ofauriculotherapy with TAS and seeds could effectively reduce the patient's pain during colposcopy.